Medication-Assisted Treatment in Problem-solving Courts: A National Survey of State and Local Court Coordinators - Farago, Fanni (Journal of drug issues, 2023)
Problem-solving courts (PSCs) are a critical part of a societal effort to mitigate the opioid epidemic's devastating consequences. This paper reports on a national survey of PSCs (N = 42 state-wide court coordinators; N = 849 local court coordinators) and examines the structural factors that could explain the likelihood of a local PSC authorizing medication-assisted treatment (MAT) and MAT utilization. Results of the analyses indicate that MAT availability at the county level was a significant predictor of the likelihood of local courts authorizing MAT. The court's location in a Medicaid expansion state was also a significant predictor of local courts allowing buprenorphine and methadone, but not naltrexone. Problem-solving courts are in the early stages of supporting the use of medications, even when funding is available through Medicaid expansion policies. Adoption and use of treatment innovations like MAT are affected by coordinators' perceptions of MAT as well as structural factors such as the availability of the medications in the community and funding resources. The study has important implications for researchers, policymakers, and practitioners.